Determination of synbiotic mango fruit yogurt and its bioactive peptides for biofunctional properties - Minj, Jagrani; Vij, Shilpa (Frontiers in Chemistry, 2025)
Yogurt is one of the most popular fermented milk products consumed worldwide. Fortification of yogurt with different food components, including fruit pulp, is a common practice to make it more palatable and healthier. In India, mango fruit is easily available. It is rich in nutrients and bioactive components. However, in-depth studies on mango fruit yogurt are scarce. Therefore, in this study, we prepared synbiotic mango fruit yogurt using response surface methodology (RSM) with three different independent factors (sugar 4%–6%; prebiotic inulin 1%–3%, and mango pulp 5%–15%) to determine the response antioxidant activity. The optimal conditions were as follows: sugar 6%, mango fruit pulp 6.562%, and prebiotic inulin 1%. There were no significant differences between the results of the experimental and predicted values of antioxidant activity by this model. The optimized product was analyzed for physicochemical, biofunctional, and technofunctional properties, including total polyphenol content, total flavonoid content, proteolytic activity, antioxidant activity, and ACE-inhibitory activity. The bioactive peptides derived from synbiotic mango fruit yogurt were also extracted (3 kDa, 5 kDa and 10 kDa) and determined for their biofunctional attributes. The antioxidant activity was recorded as 1,047.95 ± 2.20 mmol/L, 1,208.07 ± 2.92 mmol/L, and 1,293.09 ± 1.10 mmol/L Trolox equivalent antioxidant capacity, while ACE-inhibitory activity was 45.68% ± 1.23%, 64.20% ± 1.24% and 82.72% ± 1.24% inhibition in 3 kDa, 5 kDa, and 10 kDa, respectively. The 10 kDa bioactive peptide exhibited superior results than the 3 kDa and 5 kDa peptides. The synbiotic mango fruit yogurt and its bioactive peptides showed significant biofunctional activities.